Ravnateljeva vloga pri zagotavljanju kakovosti pedagoškega dela - Kozina, Ana; Vršnik Perše, Tina; Javornik Krečič, Marija; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2012)
Principals role in ensuring quality teaching. his paper focuses on the concept of quality teaching and emphasizes the role that a principal has as the administrative head and head teacher in a school. In the first part, we point out that there is no unambiguous definition of what quality of education actually is, since this is a complex phenomenon that depends on many factors. These factors are briefly introduced further on. The second part presents some of the results from the Teaching and Learning International Survey (TALIS), where we observed, among other things, what is the principals role in ensuring the quality of teaching in relation to the basic features of the school and the principal himself/herself.
Keywords: primary school; quality; principal; managing a school; instructional leadership style; administrative leadership style